Forensic Stylistic Analysis of UNNES Student’s Suicide Note - Maulida, Dini Eka; Andira, Missy Ayu; Onggatta, Reggina; Balqis, Shafiah; Hamzah, Syifa Fitri; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2023)
Suicide notes are powerful pieces of evidence in suicide cases, left as messages by individuals who commit or intend to commit suicides. The intention of leaving suicide notes is mostly to convey thoughts and feelings that are unknown to people when the victims are alive. This study investigated the linguistic features contained in the suicide note written by a college student of UNNES using descriptive-qualitative as the research method and applying Prokofyeva's theory of suicide notes linguistic features. The suicide note is available and can be accessed online. This study aimed to analyze the forensic stylistic approach towards the suicide note by showing the linguistic features and interpreting the messages delivered by the victim. The researchers classified and described the data in five distinguished characteristics of linguistic features found in the suicide note; clear reasoning, expressing emotions, text structure, grammar, and punctuation. The findings revealed that all the features are present in the suicide note, yet the researchers found that there were different tenses used in the suicide note. The results found only ellipsis in the victim’s suicide note. The data findings in this research may assist future research regarding the study of forensic stylistics, specifically in investigating suicide notes.